Prolonged membrane potential depolarization in cingulate pyramidal cells after digit amputation in adult rats - Zhuo M; Pang ZP; Wu MF; Xu ZC (SAGE Publishing, 2005)
Abstract The anterior cingulate cortex (ACC) plays an important role in higher brain functions including learning, memory, and persistent pain. Long-term potentiation of excitatory synaptic transmission has been observed in the ACC after digit amputation, which might contribute to plastic changes associated with the phantom pain. Here we report a long-lasting membrane potential depolarization in ACC neurons of adult rats after digit amputation in vivo. Shortly after digit amputation of the hind paw, the membrane potential of intracellularly recorded ACC neurons quickly depolarized from ~-70 mV to ~-15 mV and then slowly repolarized. The duration of this amputation-induced depolarization was about 40 min. Intracellular staining revealed that these neurons were pyramidal neurons in the ACC. The depolarization is activity-dependent, since peripheral application of lidocaine significantly reduced it. Furthermore, the depolarization was significantly reduced by a NMDA receptor antagonist MK-801. Our results provide direct in vivo electrophysiological evidence that ACC pyramidal cells undergo rapid and prolonged depolarization after digit amputation, and the amputation-induced depolarization in ACC neurons might be associated with the synaptic mechanisms for phantom pain.